ANALISIS RGEC UNTUK MENILAI TINGKAT KESEHATAN BANK PADA PERUSAHAAN PERBANKAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2015 - brahmayanti, sri; wahyunanti, tika (JEM17: Jurnal Ekonomi Manajemen, 2017)
ABSTRACTThis study entitled "RGEC Analysis to Assess Bank Soundness Levels in State-Owned Banking Companies Listed on Indonesia Stock Exchange for the Period 2013-2015". The 1997 and 2008 crises that caused a decline in public confidence in the Bank led the authors to conduct research on the bank's health analysis. The purpose of this research is to know the rating of Bank Soundness at State-Owned Bank (BNI, BRI, Bank Mandiri, and BTN) listed on BEI in terms of RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) in 2013-2015.This research method using descriptive with quantitative approach. The population of this study is all state banks listed in the directory of Bank Indonesia, which has an annual report period 2013 to 2015. The number of samples as many as four banks by passing through the purposive sample stage. Data collection techniques used are techniques of documentation and literature techniques. Data analysis method using RGEC method is by collecting the required data and then assess the risk profile factor that is calculate credit risk with NPL ratio and liquidity risk with LDR ratio. Then the GCG assessment conducted by self assessment by Bank. Assessment of earning factors by calculating ROA and NIM ratios and capital valuation factors using CAR ratios. The results of the analysis show that in the period 2013-2015 almost all the banks studied have a very healthy predicate except the BTN Bank is healthy. Risk Profile Factor shows the majority of bank NPLs below 5% and the majority of LDR predicated banks are quite healthy. Good Corporate Governance factor shows the bank gets very good and good predicate. Earning factor shows bank ROA more than 1.5% and NIM bank more than 3%. Capital Factor shows that bank CAR is more than 12% so it can fulfill the minimum capital requirement requirement of 8%. The general conclusion of soundness of BUMN Bank consisting of BNI, BRI, Bank Mandiri in the period of 2013-2015 using RGEC method that is Risk Profile, Good Corporate Governance, Earnings, Capital predicate VERY HEALTHY in composite rank 1, although one of the predicate of SEHAT at composite rank 2 is BTN. It is suggested for further research to expand the scope of research on bank soundness rating by using other financial ratio indicator with the latest method in accordance with Bank Indonesia Circular Letter. And for a bank that has been predicated very healthy to maintain it in the coming year.Â Keywords: Bank Health Level, NPL, LDR, GCG, ROA, NIM, CAR